Efektifitas Ekstrak Kayu Secang (Caesalpinia Sappan L.) Sebagai Bahan Pengawet Daging - Rina, Oktaf; W., Chandra Utami; Ansori, Ansori (Politeknik Negeri Lampung., 2012)
The aim of this research was to determine wood extract of secang and test usage of its as preservative in hash to microbiological test and organoleptic. Existence of component of brazilin give is specific in wood of secang that is ruddling chocolate if oxidized or in atmosphere of base. Wood extract of secang obtained of usage 1 kg of its which maserated during 144 hours were 17,6 ± 0,03. Usage of its about 1000 ppm was not yet given inhibition effect to growth of microbe in hash during inkubation about 6 hour. Colour in wood extract of secang were give change to hash colour become chocolate and influence hash organoleptic. Keywords : Wood of secang, extract, brazelein, hash